ANTIBACTERIAL ACTIVITY TEST OF 70% ETHANOL EXTRACT GINGER (Zingiber officinale) AGAINST Streptococcus mutans and Escherichia coli BACTERIA - Desi Fitriani Astuti; Kartika Sari (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Ginger (Zingiber officinale) is a herbal plant containing bioactive compounds such as flavonoids, alkaloids, saponins, tannins, and terpenoids that have the potential as natural antibacterials. This study aims to determine the antibacterial activity of 70% ethanol extract of ginger against Streptococcus mutans and Escherichia coli bacteria. The study used a laboratory experimental method with a descriptive quantitative approach. The study population was ginger plants that have the potential to be used as natural antibacterials, while the sample was fresh ginger rhizomes obtained by purposive sampling technique. Extraction was carried out using the accelerated maceration method with 70% ethanol solvent. Antibacterial activity testing was carried out using the disc diffusion method at concentrations of 1%, 3%, 5%, and 10%. The research instruments included a rotary evaporator, incubator, autoclave, micropipette, and caliper. Data were analyzed descriptively using Microsoft Excel. The results showed that ginger extract was able to inhibit the growth of Escherichia coli and Streptococcus mutans bacteria with the highest activity at a concentration of 10%. The conclusion of this study is that 70% ethanol extract of ginger has the potential as a natural antibacterial against Gram-positive and Gram-negative bacteria